2022
DOI: 10.1242/jeb.244360
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional movement of the beak during seed processing in domestic canaries

Abstract: Many songbird species rely on seeds as a primary food source and the process of picking up, positioning, cracking, dehusking, and swallowing seeds is one of the most sophisticated tasks of the beak. Still, we lack understanding about how granivorous songbirds move their beak during the different phases of seed processing. In this study, we used multi-view high speed imaging to analyze the three-dimensional movement of the beak in feeding domestic canaries. Our analysis focuses on correlation of upper and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Due to the nature of our data, we could not calculate marker‐to‐marker distance standard deviation as a measure of tracking precision (Knörlein et al, 2016). However, for a similar setup and calibration procedure, Mielke and Van Wassenbergh (2022) reported marker‐to‐marker distance standard deviations between 0.2 and 0.5 mm and, so we expect tracking precision to be similar here. As beak movements throughout the feeding act can be highly variable and irregular, five fragments of well‐tracked and relatively regular high‐frequency movements during seed positioning were selected per bird and per seed type for extraction of the kinematic metrics.…”
Section: Methodsmentioning
confidence: 57%
See 2 more Smart Citations
“…Due to the nature of our data, we could not calculate marker‐to‐marker distance standard deviation as a measure of tracking precision (Knörlein et al, 2016). However, for a similar setup and calibration procedure, Mielke and Van Wassenbergh (2022) reported marker‐to‐marker distance standard deviations between 0.2 and 0.5 mm and, so we expect tracking precision to be similar here. As beak movements throughout the feeding act can be highly variable and irregular, five fragments of well‐tracked and relatively regular high‐frequency movements during seed positioning were selected per bird and per seed type for extraction of the kinematic metrics.…”
Section: Methodsmentioning
confidence: 57%
“…The importance of beak movement implies that the force–velocity trade‐off in lever systems will become relevant (Herrel et al, 2009). Seed‐eating performance will thus depend on many factors related to the mechanical capabilities and constraints of beak movement (Herrel et al, 2009; Mielke & Van Wassenbergh, 2022). Here, we use beak kinematics to refer to basic metrics of beak movement capacity such as maximal speed, acceleration and frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the lower beak/jaw) depresses, and hence the two beak halves open or close in synchrony [1,6,7]. However, later studies showed an important level of independence in the control of upper and lower beak movement [3,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…skulls with a fixed upper beak) is not always clear, selective forces promoting cranial kinesis strongly depend on the ecological context [3]. Roles of cranial kinesis have been hypothesized in improving motion dynamics and control of food handling [1,[11][12][13][14], in sound production during singing [9] and in preventing injuries by shock absorption [1,15]. Mechanical trade-offs with other beak functions, however, cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%